Humanism In Islamic Education: Indonesian References - Usman, Abur Hamdi; Shaharuddin, Syarul Azman; Abidin, Salman Zainal (Penerbit Universiti Sains Malaysia (USM Press), 2017)
In the context of nationality, the role of education is to prepare students to face the future and promote a sense of dignity among other nations. For Indonesia, humanistic values were incorporated and formulated into Pancasila, which is often referred to as humanistic-universalistic. This paper aims to review the formulation of national education goals that are in sync with the concept of universal humanistic education. It investigates an Islamic education as an integral part of Indonesian national education can achieve both national and humanistic education goals without contradicting each other or the teachings of Islam. The finding implies that orientation of the education system in Islamic educational institutions starts with a theocentric philosophy, which emphasises the importance of the afterlife over life in this world. Throughout the educational process, students intensively explore the comprehensive teachings and practices of Islam.